Understanding personal change through storytelling in a therapeutic community - Clarke, Jenelle M. (Emerald, 2016)
Purpose: This article explores the potential for personal and community transformation through storytelling within a therapeutic community through the analysis of one narrative case study. Design/Methodology: The article uses a narrative research design to describe and theorise the individual narrative of a TC client member, “Emily”, who self-identified areas of therapeutic change. Emily’s story is a single case of personal and community transformation. Analysis focussed on story of her weight loss to understand her changing role to her self and the community. Findings: Emily’s story reveals the social complexities underpinning individual transformations within a community context. This complexity is particularly evident as Emily experienced visible weight loss but identified that the meaningful change is her changed relationship with herself and others. Using theories on symbolic interactionism, analysis of Emily’s narrative indicates the TC played a role in facilitating personal change and that through sharing her story with the wider TC, the community shifted its perspective on food and weight loss. Value: The article expands the discussion on how storytelling practices within a TC contribute to therapeutic change. It is argued that community relationships play a key role in facilitating a changed relationship with self and others, and that stories themselves play an active role in shaping community meanings.